Genetic Evaluation of Teak Clones of Allapalli Region, Maharashtra - Kumar, Anmol; Gogate, M. G.; Sharma, Rajesh; Mandal, A. K. (Indian Forester, 1997)
Availability of firsthand basic information on the genetics of important characteristics and on parental combining ability is the prerequisite for formulation an efficient breeding programme. Information on these aspects derived in Teak (Tectona grandis) indicated significant genetic variation at the family level. Height recorded both high heritability and genetic gain values. Strong correlation at the genetic level was observed between diameter and basal area. Clones A-16, A-21 and A-35 were found to be best combiners. It is suggested that these clones be used in breeding as well as in advance generation production population in Teak.